A biomimetic surface treatment to obtain durable omniphobic textiles. Issue 32 (14th May 2015) - De Marco, Carmela; Oldani, Valeria; Bianchi, Claudia Letizia; Levi, Marinella; Turri, Stefano
ABSTRACT A bio‐inspired surface treatment to make fabrics omniphobic is reported, exploiting the ability of dopamine – a widespread naturally occurring biological neurotransmitter – to give substrate adhesion and surface immobilization. Standard polyester and polyacrylonitrile fabrics, which are intrinsically rather hydrophilic, are first dip‐coated in an aqueous solution of dopamine and then treated with a fluorocarbon‐based solution. After the treatment, fabrics show a strong omniphobic behavior, while remaining quite permeable to water vapor. The efficiency of the proposed biomimetic treatment is investigated by Optical Contact Angle, Environmental Scanning Electron Microscopy (ESEM), and X‐ray Photoelectron Spectroscopy (XPS). Moreover, the mechanical durability of the surface treatment is tested through Martindale abrasion resistance measurements. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42404.